Dialectical behavior therapy for problematic behavior of the 21st century youth: Input to development of online counseling program - Ma. Fe B. Espineli; Annalyn A. Delfino (International Research Journal of Science, Technology, Education, and Management, 2021)
Suicide is a prominent cause of death among the youth. Recent evidence supports the effectiveness of dialectical behavior therapy (DBT) in lowering suicide risks. Nevertheless, existing approaches do not assist all youth. Identifying therapy response predictors can help guide therapy selection and maximize benefits. A sample of 14 Registered Guidance Counselors (RGC) was randomly selected from public and private institutions in the province of Batangas, all of which are members of the organization Philippine Guidance Counselors Association’s Batangas Chapter (PGCA-BC), and administered a self-made Likert scale questionnaire through google form due to the current situation in the country. The non-experimental descriptive correlational research design was used to look for specific relationships between three counseling techniques under DBT, namely: distress tolerance, emotion regulation, and mindfulness, and our youth’s problematic behavior such as self-harm and suicide ideation. Test of correlation reveals that distress tolerance technique and suicidal ideation have a high correlation. The same goes for emotion regulation and suicidal ideation. Moreover, hitting oneself was the most recurring manifestation of self-harm, and showing signs of anxiety, anger, or hostility was highly observed among clients with suicidal ideation. Exploring and characterizing pre-existing familial and isolated weaknesses that contribute to the youth’s heightened threat of self-destructive ideas and behaviors is necessary to provide a better understanding of such cases, to further strengthen contemporary conceptualizations, and to usher in the progress of more effectual prevention and intervention strategies in youth.